Determinants Customer Satisfaction: Multiple Moderation Models Of Service Quality At Tourist Object Gubak Hills In Islamic Business Perspective - Risya Hidayani Pratiwi; Muhammad Kurniawan; Ersi Sisdianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the impact of tourist facilities and price on customer satisfaction at Gubak Hills, with service quality as a moderating variable. Utilizing a quantitative method with a descriptive approach, the research involved 108 tourists who have visited Gubak Hills and reside in Bandar Lampung. Data was collected through questionnaires, and Smart PLS was used for structural equation modeling. The findings indicate that tourist facilities positively influence service quality, which significantly moderates the relationship between facilities and customer satisfaction. Similarly, price has a positive effect on customer satisfaction, with service quality enhancing the relationship between price and satisfaction. However, the study acknowledges limitations due to reliance on subjective perceptions, which may introduce bias and affect data accuracy. These insights are valuable for tourism managers seeking to improve visitor experiences and satisfaction at Gubak Hills.